Performance of geosynthetic-reinforced alternative sub-ballast material in a railway track. Issue 5 (October 2008) - Fernandes, G.; Palmeira, E. M.; Gomes, R. C.
Abstract : Geosynthetics have been used as reinforcement in various applications in geotechnical engineering. This paper presents a study on the use of geosynthetic reinforcement to reduce the consumption of good-quality sub-ballast material in a railway track in the state of Minas Gerais, Brazil. Six test sections on the railway were instrumented and monitored for a period of 2 years. Nonwoven geotextile and a geogrid were used as reinforcement in different positions in the sub-ballast. The results obtained showed that the presence of geosynthetic reinforcement reduced the strains mobilised in the sub-ballast, reduced the breakage of ballast element, and allowed the use of a cheaper alternative material in the sub-ballast construction. The results showed the potential of the use of alternative sub-ballast material reinforced with geosynthetic to reduce the costs of construction and maintenance of railway tracks.